NEW DEVONIAN BRYOZOANS FROM MONGOLIA - Gorjunova R.V.; Weiss O.B. (My University, 2003)
Two new genera, Fistuliphragmoides, with its type species F. gobiensis sp. nov., from the Emsian of southern Mongolia and Boardmanella, with its type species B. richardi sp. nov., from the Givetian of eastern Mongolia are described. In addition to the type species, the genus Boardmanella contains Batostomella interporosa Ulrich et Bassler, 1913; Dyscritella devonica Volkova, 1974; D. antiqua Nekhoroshev, 1977; D. indistincta Nekhoroshev, 1977; Leptotrypella inennis Kopaevich, 1984; L. uniserialis Kopaevich, 1984; and L. superba Kopaevich, 1984.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская